2018
DOI: 10.1021/acs.jpcc.8b07524
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Transfer Mechanism of Photogenerated Carriers for WO3/TiO2 Heterojunction Photocatalysts: Is It the Transfer of Band–Band or Z-Scheme? Why?

Abstract: The transfer mechanism of photoexcited charge carriers is always a hot topic in the photocatalysis research field. Coupling a photocatalyst with other photocatalysts is one of the most widely used strategies to realize effective transfer of the photogenerated carriers. In the study, a series of WO3/TiO2 composites with different weight ratios were prepared. The WO3/TiO2 composites were characterized in detail. The result showed that regardless of whether the primary part of WO3/TiO2 composites is TiO2 or WO3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 86 publications
4
56
0
Order By: Relevance
“…In IS, two peaks at 161.3 eV, 162.6 eV were deconvoluted, corresponding to S 2+ 2p 3/2 and S 2p 1/2 , 40,41 respectively. With respect to BTIS, besides the two peaks at 161.3 eV and 162.6 eV which are respectively attributed to S 2+ 2p 3/2 and S 2p 1/2 in the location far from the heterojunction of BT@IS, there are still two additional peaks at 160.0 eV and 162.4 eV were tted, also ascribed to S 2p 3/2 and S 2p 1/2 in the heterojunction of BT@IS, 38,39 respectively.…”
Section: Phases and Microstructuresmentioning
confidence: 97%
See 1 more Smart Citation
“…In IS, two peaks at 161.3 eV, 162.6 eV were deconvoluted, corresponding to S 2+ 2p 3/2 and S 2p 1/2 , 40,41 respectively. With respect to BTIS, besides the two peaks at 161.3 eV and 162.6 eV which are respectively attributed to S 2+ 2p 3/2 and S 2p 1/2 in the location far from the heterojunction of BT@IS, there are still two additional peaks at 160.0 eV and 162.4 eV were tted, also ascribed to S 2p 3/2 and S 2p 1/2 in the heterojunction of BT@IS, 38,39 respectively.…”
Section: Phases and Microstructuresmentioning
confidence: 97%
“…It is reported that built-in electric elds in the heterojunctions WO 3 /TiO 2 and CdSe/CdTe could would result in the shi of binding energy. 39,40 Therefore, the shi to higher binding energy for In 3+ 3d 5/2 and In 3+ 3d 3/2 could be ascribed to the heterojunction BT@IS. Fig.…”
Section: Phases and Microstructuresmentioning
confidence: 98%
“…[5][6][7] On the other hand, exploration of explicit charge carrier migration pathways/ directions can deepen our understanding of the complicated physical phenomena and catalytic reactions involving charge transfer processes. 1,8 The construction of semiconductor heterojunctions with staggered band gap alignment is an effective strategy to promote the separation of photogenerated charge carriers and study charge migration dynamics. [9][10][11][12] However, it remains challenging to achieve the desired charge separation efficiency and deeply understand the charge migration direction based on the information available for conventional semiconductor heterojunctions commonly synthesized by multistep procedures and comprising size-variable interfacial phases with a relatively unclear interface location, complicated interface structures, and randomly positioned dopants (Scheme 1a, b and e).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] However, the photocatalytic activity of these composite catalysts is still low and far from practical applications due to the limited light response range and fast recombination of the photogenerated carriers. [10][11][12] Developing novel composite systems or novel composite structures are effective strategies to improve the photocatalytic performance of the photocatalytic materials. [13,14] The unique structure of multicomponent composite provides a basis for the structural design of high performance composite photocatalyst.…”
Section: Introductionmentioning
confidence: 99%